2004
DOI: 10.1152/ajpheart.00199.2003
|View full text |Cite
|
Sign up to set email alerts
|

Progressive apoptotic cell death triggered by transient oxidative insult in H9c2 rat ventricular cells: a novel pattern of apoptosis and the mechanisms

Abstract: Many pathophysiological processes are associated with oxidative stress and progressive cell death. Oxidative stress is an apoptotic inducer that is known to cause rapid cell death. Here we show that a brief oxidative insult (5-min exposure to 400 microM H(2)O(2)), although it did not kill H9c2 rat ventricular cells during the exposure, triggered an intracellular death cascade leading to delayed time-dependent cell death starting from 1 h after the insult had been withdrawn, and this post-H(2)O(2) cell death cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…Cell index of the absolute control cells that did not receive H 2 O 2 treatment remained constant for 20 h, but began to decline thereafter, probably due to the overgrowth of culture in the well. Vehicle-control cells (which received H 2 O 2 and vehicle, but no treatment with cytoprotective compounds), showed a rapid decline of cell index, presumably as a consequence of cell shrinkage after oxidative stress (20) that is detected by the real-time cell microelectronic sensing system. At later time points, inhibition of cell viability, proliferation and death are also likely to contribute to the decline in cell index.…”
Section: Continuous Determination Of Cell Viability During Oxidative mentioning
confidence: 99%
“…Cell index of the absolute control cells that did not receive H 2 O 2 treatment remained constant for 20 h, but began to decline thereafter, probably due to the overgrowth of culture in the well. Vehicle-control cells (which received H 2 O 2 and vehicle, but no treatment with cytoprotective compounds), showed a rapid decline of cell index, presumably as a consequence of cell shrinkage after oxidative stress (20) that is detected by the real-time cell microelectronic sensing system. At later time points, inhibition of cell viability, proliferation and death are also likely to contribute to the decline in cell index.…”
Section: Continuous Determination Of Cell Viability During Oxidative mentioning
confidence: 99%
“…19) On the other hand, ROS has been reported to activate caspase-3 and promote apoptotic cell death. 20) We observed the activation of caspase-3 and DNA fragmentation by CoCl 2 treatment, and these phenomena were significantly inhibited by pre-treatment with NAC (Figs. 3A, B).…”
Section: Discussionmentioning
confidence: 78%
“…Vitamin D 3 along with its metabolites influences directly or indirectly almost all metabolic processes such as proliferation, differentiation, apoptosis, inflammatory processes, and mutagenesis. Such multifactorial effects of vitamin D 3 can be a profitable source of new therapeutic solutions for two radically divergent diseases as cancer and neurodegeneration [134]. The discussed results could be relevant in the light of the use of vitamin D 3 to promote supplementation or to adjust therapeutic strategies in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 93%
“…Recent investigations on cardiac myocytes showed that ROS produced by mitochondrial and oxidative stress can cause multiple changes in the cell structure and the function that are associated with a failing heart [133] and apoptosis [134] or autophagy [135]. On the other hand, ROS, along with NO, show antiapoptotic effects involving several signaling pathways; for example, not only activates proapoptotic signals [135] but also potently induces autophagy [136].…”
Section: Protective Effects Of Vitamin Dmentioning
confidence: 99%